Breaking Barriers to Digital Adoption: A Case Study of Paddy Farmers in West Kalimantan - Bancin, Hardi Dominikus; Sirait, Resmaya Agnesia Mutiara; Sugiardi, Sigit (Jurnal AGRISEP, 2025)
The adoption of digital agricultural technologies is regarded as a pivotal measure for enhancing productivity and efficiency in Indonesia's paddy farming sector. This research is concerned with the factors that influence the adoption of digital technologies among paddy farmers in Kubu Raya Regency, West Kalimantan. A quantitative approach was employed in the study, which involved 150 farmers. The role of government support, farmer characteristics, mentoring, and perceptions in promoting agricultural digitalisation was analysed. The findings indicate that the role of the government, particularly in the development of infrastructure and the provision of financial assistance, is the most significant factor influencing the adoption of digital technologies. Mentoring programs, in particular those that concentrate on the spheres of education and motivation, also assume a pivotal role. However, contrary to expectations, farmers' perceptions alone do not significantly impact their decision to adopt digital technologies. This suggests that, while attitudes towards technology are favourable, structural and educational support are vital for effective implementation. The study concludes that the key factors in fostering digital transformation in the region's agricultural sector are the enhancement of infrastructure, the provision of targeted training, and the offering of financial incentives.